64.6k views
1 vote
-4x - 9y = 26

8x +9y = -34
Add to eliminate y.
Subtract to eliminate y.
Add to eliminate x.
Subtract to eliminate x.

User Rooby
by
5.3k points

2 Answers

5 votes

Answer:

Add to eliminate y

Explanation:

This is because you'll want to add

-4x -9y = 26

8x +9y = -34

to get rid/eliminate the y

The reason why it's not subtract it because the it'll become

-4x-9y=26

-8x-9y=34

which makes the y-values not the reciprocal of each other and you wouldn't be able to eliminate the y.

And it's neither of the add or subtract to eliminate x because the numbers need to be the same numbers and reciprocal of each other

ex:

4 and -4

or

8 and -8

or

-10 and 10

User Realuser
by
4.9k points
2 votes

Answer:

add to eliminate y

Explanation:

Because the one y is negative, you would add it to the positive y to eliminate both. A positive plus a negative is the same as subtracting from the positive number.

ex:
10+-5=5 because
10-5=5

hope this makes sense :)

User Chooks
by
5.9k points